The mechanism of formation connections of wood and wood materials at use of glutinous compositions on the basis of polyvinylacetates (PVA) dispersions - Solonynka , Vasyl (Forestry, Forest, Paper and Woodworking Industry, 2024)
The analysis the mechanism of formation connections of wood and wood materials by glues on a basis PVA dispersions is resulted. Influence of separate compound components of a composition on formation of glutinous communication is described.